Anterior Cervical Discectomy and Fusion Versus Cervical Disc Replacement in Patients With Significant Cervical Spondylosis. Issue 2 (March 2022) - Alluri, Ram Kiran; Vaishnav, Avani S.; Fourman, Mitchell S.; Sivaganesan, Ahilan; Lee, Ryan; Urakawa, Hikari; Mok, Jung Kee; Sato, Kosuke; Albert, Todd A.; Huang, Russel C.; Sheha, Evan D.; Gang, Catherine Himo; et al.
Abstract : Study Design: Retrospective cohort study. Objective: The aim was to compare clinical outcomes in patients with significant cervical spondylosis treated with cervical disc replacement (CDR) compared with anterior cervical discectomy and fusion (ACDF). Summary of Background Data: As CDR utilization has increased over the past decade, recent studies have investigated the outcomes of CDR in patients with more significant spondylotic changes and demonstrated improved postoperative patient-reported outcomes (PROs). However, no prior study has investigated clinical outcomes of patients with significant spondylotic changes treated with CDR in comparison to ACDF. Methods: Patients who underwent 1-level or 2-level CDR or ACDF with significant cervical spondylosis, quantified using a validated grading scale, were identified, and prospectively collected data was retrospectively reviewed. The following PROs were analyzed: Neck Disability Index (NDI), visual analog scale-Neck, visual analog scale-Arm, and PROMIS Physical Function (PROMIS-PF) Computer Adaptive Test Score. Demographic, operative, and radiographic variables, and achievement of minimum clinically important difference (MCID) for each PRO were compared between the 2 groups. Results: A total of 66 patients were included in the present study, of which 35 (53%) were treated with CDR and 31 (47%) with ACDF. The preoperative cervical spondylotic grade was similar between the 2 groups (1.8 vs. 2.2, P =0.27). At final follow-up, there was no significant difference in the absolute value for each PRO between the 2 groups ( P >0.19) and both groups demonstrated significant improvement in each PRO compared with preoperative values ( P <0.01). There was no significant difference in the percentage of patients achieving the MCID for each PRO when comparing CDR to ACDF ( P >0.09). Conclusions: A similar percentage of patients with significant degenerative cervical spondylosis achieved the MCID across multiple PROs when treated with CDR or ACDF. Patients in both treatment groups demonstrated significant improvement in all PROs assessed when compared with preoperative values. Level of Evidence: Level III.